Excercising power in the self-management of COPD: A narrative inquiry. Patient and user perspectives - Huntley-Moore, Sylvia (My University, 2023)
Objective: To develop an in-depth understanding of how people with COPD exercise power in the self- management of their illness. Methods: This was a narrative inquiry using Foucault’s concepts of power, knowledge and agency as a conceptual framework. Up to three unstructured interviews were conducted with 31 people with COPD in the Republic of Ireland. Thematic template analysis was used to analyse the data. The COREQ checklist was used to report this qualitative study. Results: The findings of the study show that participants exercised power through mobilising agency in two main ways. They resisted the imposition of power by leveraging different types of knowledge. They also engaged in practices designed to operate on the self and the body in order to achieve happiness and health. However, this agency was constrained by the imposition of power by health care professionals. Conclusion: The findings expand the understanding of self-management as a complex and multi-dimensional concept that is negotiated and constructed by people with COPD, using their own knowledge and agency. Practice implications: Honouring the considerable skills and resources that people with COPD mobilise to self- manage should form the heart of person-centred self-management support.
PUBLISHED
Keywords: Chronic obstructive pulmonary disease, COPD, Self-management, power, agency, narrative inquiry; Chronic Health Condition